Integrating Spirituality, Ethics, and Innovation in Islamic Educational Leadership: A Holistic Model from Indonesian Secondary Education - Nur Asiah; Yudesta Erfayliana; Hasan Sastra Negara; Harjoni Desky (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2025)
This study advances Islamic educational leadership theory by examining the integration of spirituality, ethics, and innovation as a holistic leadership model in Islamic secondary education. Using an explanatory sequential mixed-methods design, the research was conducted at MAN 1 Bandar Lampung. Quantitative data were collected from 120 teachers and staff to measure leadership practices across spiritual, ethical, and innovative dimensions. Regression analysis showed that spirituality and ethics were the strongest predictors of leadership effectiveness, while innovation, although positively perceived, had a relatively weaker influence. To deepen these findings, qualitative data were obtained through semi-structured interviews, complemented by document analysis. Thematic analysis revealed that leadership practices are strongly rooted in spiritual awareness, moral integrity, and participatory decision-making, reflecting fundamental Islamic values. Innovation was mainly evident in instructional practices, such as blended learning and the use of digital platforms, but was less integrated into administrative and organizational leadership. Identified challenges included limited technological infrastructure, uneven digital literacy, and resistance to organizational change. This study proposes a holistic and transferable framework of Islamic educational leadership in which spirituality provides moral orientation, ethics ensures accountability and justice, and innovation supports adaptive responses to contemporary challenges. The findings contribute to leadership theory by highlighting that transformational change in Islamic educational settings is primarily guided by spiritual and ethical accountability rather than managerial efficiency alone, offering valuable insights for leadership development and policy formulation in Islamic education beyond the local context.